2022
DOI: 10.7759/cureus.28056
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of CD44+/CD24- and Aldehyde Dehydrogenase Enzyme Markers in Cancer Stem Cells as Prognostic Indicators for Triple-Negative Breast Cancer

Abstract: Triple-negative breast cancer (TNBC) has been extensively studied not just for its aggressive behavior but also to understand its complex molecular nature. This type of heterogeneous tumor shows no expression of estrogen receptor (ER) or progesterone receptor (PR) and does not express the HER2 gene, and often these tumors are high grade with distinct histological groups. The basal-like subtype is most commonly related to the TNBC type of neoplasms; it can be further classified according to Lehmann and Burstein… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 65 publications
0
3
0
Order By: Relevance
“…The contradicted findings reported in the current study concerning the expression of CD24 as a marker of stemness within the breast cancer TME come in line with previous studies’ findings. Several studies had reported that breast CSCs population express C44 + /CD24 − surface markers and that their abundance is correlated with recurrence, metastasis, and therapy resistance [ 35 , 36 ]. Unlike CD44, CD24 was reported to be more expressed on differentiated breast cancer cells rather than progenitor cancer stem cells [ 37 ].…”
Section: Discussionmentioning
confidence: 99%
“…The contradicted findings reported in the current study concerning the expression of CD24 as a marker of stemness within the breast cancer TME come in line with previous studies’ findings. Several studies had reported that breast CSCs population express C44 + /CD24 − surface markers and that their abundance is correlated with recurrence, metastasis, and therapy resistance [ 35 , 36 ]. Unlike CD44, CD24 was reported to be more expressed on differentiated breast cancer cells rather than progenitor cancer stem cells [ 37 ].…”
Section: Discussionmentioning
confidence: 99%
“…In breast cancer, CD44 plays key roles in aggressive tumor behavior, 56 tumor progression, 57 CSCs trait induction, 58 , 59 and prognosis. 60 Rokana et al.…”
Section: Cd44 In Neoplastic Diseasesmentioning
confidence: 99%
“…As the most prevalent marker for CSCs, CD44’s expression is directly linked with the self-renewal and tumorigenic capacity of CSCs, contributing significantly to tumorigenesis ( 11 ). Numerous studies have indicated that heightened CD44 expression can escalate the tumorigenic potential in various cancers such as colorectal ( 12 ), breast ( 13 ) and gastric ( 14 ) cancers. Moreover, CD44 is extensively overexpressed in other cancer types like ovarian cancer ( 15 ) and oral squamous carcinoma ( 16 ), in which it is associated with aggressive biological behavior leading to a poor prognosis.…”
Section: Introductionmentioning
confidence: 99%